Do Disadvantageous Social Contexts Influence Food Choice? Evidence From Three Laboratory Experiments - Rramani, Qëndresa; Gerhardt, Holger; Grote, Xenia; Zhao, Weihua; Schultz, Johannes; Weber, Bernd (Frontiers in Psychology, 2020)
Increasing rates of obesity have fueled interest in the factors underlying food choice. While epidemiological studies report that disadvantaged social groups exhibit a higher incidence of obesity, causal evidence for an effect of social contexts on food choice remains scarce. To further our knowledge, we experimentally investigated the effect of disadvantageous social context on food choice in healthy, non-dieting participants. We used three established experimental methods to generate social contexts of different valence in controlled laboratory settings: (i) receiving varying amounts of money in a Dictator Game (DG; n = 40), (ii) being included or excluded in a Cyberball Game (CBG; n = 35), and (iii) performing well, average, or poorly in a response time ranking task (RTR; n = 81). Following exposure to a particular social context, participants made pairwise choices between food items that involved a conflict between perceived taste and health attributes. In line with previous research, stronger dispositional self-control, greater cognitive control of eating behavior, and lower external eating (all assessed via questionnaires) were associated with healthier food choices. As expected, being treated unfairly in the DG, being excluded in the CBG, and performing poorly in the RTR led to negative emotions. However, we did not find an effect of the induced social context on food choice in any of the experiments, even when taking into account individual differences in participants' responses to the social context. Our results suggest that-at least in controlled laboratory environments-the influence of disadvantageous social contexts on food choice is limited.